Direct visualization of receptors for thyrotropin-releasing hormone with a fluorescein-labeled analog. - Halpern, J (1981)
Thyrotropin-releasing hormone (TRH) binds to specific receptors on GH4C1 pituitary tumor cells. A fluorescently labeled analog of TRH was synthesized by coupling pGlu-His-ProNH(CH2)6NH2 to fluorescein isothiocyanate. The fluorescein-labeled peptide (FL-TRH) stimulated prolactin synthesis and release by GH4C1 cultures and bound to TRH receptors with an apparent Kd of 400 nM. Binding of FL-TRH to unfixed, viable GH4C1 cells was followed by fluorescence microscopy. After incubation with 1.4 microM FL-TRH for 1 hr at 37 degrees C, the surface of all cells was fluorescent and patches of intense fluorescence were evident. Control cultures incubated with FL-TRH and excess TRH were not fluorescent, and a line of pituitary tumor cells which lacks TRH receptors displayed little fluorescence after incubation with FL-TRH. When GH4C1 cells were incubated with FL-TRH for 1 hr at 37 degrees C and then with excess TRH for an additional 1 hr, the fluorescence associated with the cells was diminished to control levels. The results demonstrate that the fluorescein-labeled peptide labels specific TRH receptors.